Prevalence of depression and anxiety in patients with chronic obstructive pulmonary disease and their association with psychosocial outcomes: A cross-sectional study from Pakistan. (October 2021) - Husain, Muhammad Omair; Chaudhry, Imran B; Blakemore, Amy; Shakoor, Suleman; Husain, Muhammad Ali; Lane, Steven; Kiran, Tayyeba; Jafri, Farhat; Memon, Rakhshi; Panagioti, Maria; Husain, Nusrat
Objectives: Chronic obstructive pulmonary disease contributes to substantial health and economic burden worldwide. Co-morbid depression and anxiety are highly prevalent in patients with chronic obstructive pulmonary disease. Depressive symptoms in chronic obstructive pulmonary disease are associated with poorer survival, longer hospitalisation and impaired quality of life. Literature on chronic obstructive pulmonary disease is largely derived from high-income countries; yet 90% of deaths related to chronic obstructive pulmonary disease occur in low- and middle-income countries. We aimed to establish the prevalence of anxiety and depression in patients with chronic obstructive pulmonary disease, as well as the association with psychosocial outcomes. Methods: This was a cross-sectional study of chronic obstructive pulmonary disease patients attending outpatient primary care clinics in Karachi, Pakistan. The Patient Health Questionnaire-9 was used to assess depression and the Generalised Anxiety Disorder-7 scale was used for the assessment of anxiety. Health-related quality of life was assessed with EuroQol–Five Dimensions, social support with Oslo-3 and social stress with Life Events Checklist. We recruited 293 subjects. Results: The prevalence of depression and anxiety in the sample was 51% ( n = 149) and 20% ( n = 59), respectively. Depressed chronic obstructive pulmonary disease patients reported significantly lower health-related quality of life scores as compared to non-depressed patients. Participants with depression had significantly higher levels of anxiety, less social support, higher social stress and more subjective impairment in quality of life. Conclusion: Given the association with reduced social support and increased perceived stress, the role of psychosocial interventions must be explored in improving outcomes of chronic obstructive pulmonary disease patients in Pakistan.